Pandangan Masyarakat Terhadap Kitab Perukunan Karya H. Abdul Rasyid - Siti Sarah Aulia Husnah; H. Arifinsyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Review of People's Views on the Book of Harmony by H. Abdul Rasyid. Both the younger and older generations tend to benefit from the phenomenon of public perception of the book on harmony by H. Abdul Rasyid. psychologically healthy, which can affect the social life of its followers. The aim of this research is to provide a broad overview of the many factors that influence people's behavior in societies that implement Islamic Sharia. Research findings reveal the factors that encourage people to comply with the KaryaH Kunan Book. Rasyid Abdul, this is 1) because of curiosity and increasing knowledge in reading Arb-Malay. 2) because he wants to do da'wah, namely fasting Zuhud. 3) those who want to expand the teachings of the scriptures that have been passed down from generation to generation. 4) individuals who are given direction by Allah SWT to perfect and translate their inadequate prayer sessions. The fact is that the Community's View of the Book of Harmony by H. Abdul Rasyid was formed to enable the Sidodadi community to improve their worship.